2021
DOI: 10.5433/1679-0359.2021v42n3supl1p2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of extracted polyphenols from black and green tea wastes on in-vitro fermentability of feed ingredients

Abstract: The effect of using black and green tea waste extracts on the diet nutritional value was investigated with three methods of in vitro degradability, gas production, and McNiven’s enzymatic digestion in the present experiment. Total phenolic compounds and total tannin for green tea extract were 20.3% and 14.8% of dry matter (DM), respectively, and for black tea were 18.7% and 12.7% of dry matter, respectively. The addition of green and black tea waste extracts reduced both gas production during incubation hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Despite this, many studies have found that tannins may negatively affect the digestibility of diets. As tannins are interpreted differently depending on their type, origin, and supplement levels, their influence on ruminal protozoa, bacteria, fungi, and methanogens varies [ 13 ]. According to Petlum et al [ 14 ], molecular weight greatly influences the effectiveness of condensed tannins as ruminal methane inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, many studies have found that tannins may negatively affect the digestibility of diets. As tannins are interpreted differently depending on their type, origin, and supplement levels, their influence on ruminal protozoa, bacteria, fungi, and methanogens varies [ 13 ]. According to Petlum et al [ 14 ], molecular weight greatly influences the effectiveness of condensed tannins as ruminal methane inhibitors.…”
Section: Introductionmentioning
confidence: 99%